Current Strategies for Promoting the Large-scale Production of Exosomes - Qu, Qing; Fu, Bin; Long, Yong; Liu, Zi-Yu; Tian, Xiao-Hong (Current Neuropharmacology, 2023)
Exosomes, as nanoscale biological vesicles, have been shown to have great potential for biomedical applications. However, the low yield of exosomes limits their application. In this review, we focus on methods to increase exosome yield. Two main strategies are used to increase exosome production, one is based on genetic manipulation of the exosome biogenesis and release pathway, and the other is by pretreating parent cells, changing the culture method or adding different components to the medium. By applying these strategies, exosomes can be produced on a large scale to facilitate their practical application in the clinic.
Keywords: exosome production